HEALTH INFORMATION SYSTEMS IN A DEVELOPING COUNTRY (CASE STUDY OF E-HEALTH SYSTEM IN A NIGERIAN HOSPITAL) - Abubakar, Umar Faruk (European Scientific Journal, ESJ, 2015)
Health Information Systems (HIS) are one of the six essential and interrelated building blocks of a health system. A well-functioning HIS no doubt enhances accurate, timely and reliable information on health status and health care determinants required for and efficient and effective clinical and managerial decision making. In developing countries Application of HIS and e-health is in the increase. The analysis of Health Information systems in developing countries highlights areas of Challenges and areas needing Improvement.